2021
DOI: 10.1007/s40544-021-0492-2
|View full text |Cite
|
Sign up to set email alerts
|

Water-based lubrication of niobium nitride

Abstract: Water-based lubrication has attracted wide attention as an oil-free lubrication method owing to its greener and cleaner lubrication means. However, due to operating in the water environment, most moving parts would inevitably suffer from abrasion, rusting, and aging problems. Developing a novel solid-water composite system with ultra-low friction and wear will open new possibilities for innovative lubrication material research and development. Here, we first revealed the water-based lubrication behavior of a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…There were some experimental studies that resulted in the similar data as shown in Figure 23. [ 190,194,195 ]…”
Section: Surface Properties and Applications Of Tmnsmentioning
confidence: 99%
See 2 more Smart Citations
“…There were some experimental studies that resulted in the similar data as shown in Figure 23. [ 190,194,195 ]…”
Section: Surface Properties and Applications Of Tmnsmentioning
confidence: 99%
“…In this regard, the authors suggested that nitrides of group 5B elements of the periodic table such VN, NbN, and TaN could serve as a nonadditive water–solid composite advanced lubricating materials due to their low friction and wear rate. [ 195 ]…”
Section: Surface Properties and Applications Of Tmnsmentioning
confidence: 99%
See 1 more Smart Citation
“…Water-based lubricants can reduce friction effectively between workpieces, reduce machine wear, save energy and improve machine efficiency. It is one of the most promising lubricants today (Deng et al , 2016; Miao et al , 2021). Vegetable oil is a potential environmentally friendly metal cutting fluid, which is harmless to the human body and solves a series of health problems caused by synthetic cutting fluids (R et al , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The TiNbWN thin film can be described as a TiN-type single fcc phase (PDF#28-1420), in which the Nb and W atoms occupy the Ti sites. The fact that the TiNbWN film contains a single solution phase can be supported by the structural similarities of the binary nitrides of TiN, NbN, and γWN, which exhibit the same fcc phase with rather similar lattice parameters (a (TiN) = ~0.42 nm, a (NbN) = ~0.44 nm, and a (γWN) = ~0.41 nm)[45][46][47]. The characteristic peaks in the XRD pattern slightly deviated to smaller values compared with that of the TiN phase, indicating that the interplanar spacing of the fcc solution in the TiNbWN thin film was increased by dissolving Nb and W. The strongest peak corresponded to the (111) crystallographic plane, implying the preferred growth of the film deposited.…”
mentioning
confidence: 99%